From movements to words: action monitoring in the medial frontal cortex along a caudal to rostral prediction error gradient - Dorokhova, Lydia; Shiqing, Shen; Morgane, Peirolo; Jean-Luc, Anton; Bruno, Nazarian; Julien, Sein; Valérie, Chanoine; Pascal, Belin; Loh, Kep Kee; Elin, Runnqvist (Journal of neurolinguistics, 2025)
Speech error monitoring recruits the medial frontal cortex (MFC) region in the human brain. Error monitoring-related activity in the MFC has been interpreted both in terms of conflict monitoring and feedback-driven control, but as similar regions of the MFC are implicated in various levels of behavioral control ranging from basic motor movement control to high-level cognitive control functions, a more comprehensive account is needed. Moreover, as speech errors and other actions that involve varying control demands engage a widespread yet partially overlapping set of regions of the MFC, such an account should ideally explain the anatomical distribution of error-related functional activations within the MFC. Here we wanted to assess the hypothesis that the MFC has a similar role in the evaluation of action outcomes for motor and mental actions, operating along a rostral-caudal gradient of higher-lower degree of cognitive control demands involving prediction errors from both sensory and epistemic sources. To this end, we conducted an individual-specific annotation of task-fMRI BOLD activation peaks related to overt speech error monitoring (i.e. that involve the largest degree of cognitive control demands, Study I and II), tongue movement monitoring (i.e. that involve an intermediate degree of cognitive control demands) and tongue movement (i.e. that involve the lowest degree of cognitive control demands, Study II) in the MFC region. Results revealed overlapping clusters across the three contrasts across the MFC, but importantly both the number of peaks and their relative position along the rostral caudal axis were consistent with a hierarchical rostral caudal processing gradient in the MFC. While tongue movement showed more caudal activation in the MFC, overt speech error monitoring showed more rostral activation, and tongue movement monitoring patterned in between. Furthermore, the combined results of both studies suggested that activation peaks were located more dorsally for participants that had a paracingulate gyrus, replicating a previously documented effect for movement and further supporting a common functional role of the MFC across very distinct actions. •Reveals a caudal-to-rostral gradient in the medial frontal cortex for motor and cognitive control.•Demonstrates overlapping neural mechanisms for monitoring both motor actions and speech errors.•Shows the influence of sulcal morphology on medial frontal cortex activation patterns.•Proposes a unified framework for action monitoring across diverse levels of control, from movements to words.